Characteristics of Concrete with Sedimentary Rock Aggregate - N. L. Poleyko; S. N. Kovshar; R. F. Osos; D. N. Poleyko (Наука и техника)
The paper presents results of the investigations of concrete on crushed fluxing limestone, which is a secondary product of the metallurgical industry. The main physical and mechanical and operating characteristics of concrete on fluxing limestone have been studied. It has been ascertained on the basis of the conducted investigations that fluxing limestone can be used for products and constructions made of heavy-weight concrete along with such aggregates as crushed granite stone and natural gravel